Peran KKN Tematik dalam Penguatan Literasi dan Pemberdayaan Masyarakat Desa Badirih - Heni Dea Simanjuntak; Wafik Andini; Fendy Hariatama H (Universitas Muhammadiyah Jember, 2025)
Regular Thematic Real Work Lecture (KKN-TR) Group 187 Palangka Raya University was held in Badirih Village as an effort to strengthen literacy and community empowerment through participatory and local potential approaches. The main program includes the management of village libraries, gemes activities (fond of reading together), literacy visits to schools, typing training, and health programs such as PHBS and Posyandu. The implementation method refers to the Participatory Action Research (PAR) approach and Asset-Based Community Development (ABCD), which emphasizes the active involvement of the community in each stage of activity. The results showed a significant increase in children's reading interest, student typing skills, and citizen participation in toddler and elderly health services. The impact of the program is not only reflected in quantitative data, but also changes in the mindset of the community towards the importance of literacy and health. This program has proven effective in supporting the achievement of Sustainable Development Objectives (SDGs), especially in the field of quality education (SDG 4) and good health (SDG 3).